New species of Laparocerus Schönherr, 1834 (Coleoptera, Curculionidae) from the island of Tenerife (Canary Islands) - Machado, Antonio (Zootaxa, 2007)
The weevil genus Laparocerus Schönherr (1834) is distributed and very diverse in the Macaronesian region. In advance of a larger monographic study of the genus, five new species endemic to the island of Tenerife (Canary Islands) are described in this first contribution: L. tinguaro n.sp., L. boticarius n.sp., L. chasnensis n.sp., L. aguiari n.sp., and L. subparallelus n.sp. Detailed descriptions (including photographs of holotypes and drawings of aedeagus, spermatheca, and sternite VIII) are supplemented with diagnostic remarks referring to similar or related taxa. Data on the distribution within the island, phenology, and the host-plants are also provided. A total of 697 specimens have been studied.